Validity and Reliability Determination of the Persian Version of Prosthesis Evaluation in Individuals with Lower Limb Amputations Questionnaire - M. Adel Gomnam; M. Kamali; H. Mobaraki; H. Saeedi (طب جانباز, 2016)
Aims: Post-amputation rehabilitation can improve the quality of life. Prosthesis evaluation questionnaire (PEQ) has been designed to evaluate the prosthetic functioning and major aspects of the quality of life in persons with lower-limb amputations. The aim of this study was to translate the questionnaire into Persian and evaluate validity and reliability of the translation.